2004
DOI: 10.1063/1.1824033
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cholesterol on voids in phospholipid membranes

Abstract: Free volume pockets or voids are important to many biological processes in cell membranes. Free volume fluctuations are a prerequisite for diffusion of lipids and other macromolecules in lipid bilayers. Permeation of small solutes across a membrane, as well as diffusion of solutes in the membrane interior are further examples of phenomena where voids and their properties play a central role. Cholesterol has been suggested to change the structure and function of membranes by altering their free volume propertie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
137
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(150 citation statements)
references
References 46 publications
(94 reference statements)
13
137
0
Order By: Relevance
“…Generally, we can distinguish between (i) global effects of the perturbed lipid bilayer, discussed in the previous section, on membrane protein behavior and (ii) specific effects of cholesterol binding to defined binding motifs on membrane proteins. The increased order of the lipid acyl chains results in a reduction of free volume in bilayers when cholesterol is introduced (Falck et al, 2004). This increased free volume changes the conformational behavior and shifts conformational equilibria of membrane proteins in the presence of cholesterol.…”
Section: Cholesterol Modulates the Structure And Activity Of Integralmentioning
confidence: 99%
“…Generally, we can distinguish between (i) global effects of the perturbed lipid bilayer, discussed in the previous section, on membrane protein behavior and (ii) specific effects of cholesterol binding to defined binding motifs on membrane proteins. The increased order of the lipid acyl chains results in a reduction of free volume in bilayers when cholesterol is introduced (Falck et al, 2004). This increased free volume changes the conformational behavior and shifts conformational equilibria of membrane proteins in the presence of cholesterol.…”
Section: Cholesterol Modulates the Structure And Activity Of Integralmentioning
confidence: 99%
“…Relative volume fluctuations of PLFE liposomes at any given temperature examined were 1.6–2.2 times more damped than those found in DPPC liposomes [50]. Volume fluctuations are closely related to solute permeation across lipid membranes [51] and lateral motion of membrane components [52]. Thus, the low values of relative volume fluctuations explain why PLFE liposomes exhibit unusually low proton permeation and dye leakage [45, 46] as well as limited lateral mobility, especially at low temperatures (e.g., <26°C) [43, 53].…”
Section: Physical Properties Of Model Membranes Composed Of Thermomentioning
confidence: 99%
“…A semi-isotropic scheme for pressure control was employed, and the particle mesh Ewald method (38) was used for electrostatics. A more detailed description of the simulation protocol used in this study can be found elsewhere (39,40).…”
Section: Methodsmentioning
confidence: 99%